IDENTIFIKASI MASALAH DALAM PENDAYAGUNAAN MESIN DAN PERALATAN INDUSTRI KAKAO DI KUB LINTAS SEKAYAM KABUPATEN SANGGAU - Setyo Utomo, Rudy; Sujana, Ivan (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2016)
Equipment and machinery cocoa processing in KUB Lintas Sekayam not utilized properly. This study aimed to identify the factors that cause not usefulness the machinery and equipment in KUB Lintas Sekayam at Sanggau Regency in the process of cocoa processing production. Availability of raw materials, capital, labor, cocoa market, trade and management of KUB Lintas Sekayam also identified. The results showed that were 34 machines and equipments already exist in KUB Lintas Sekayam. Between them, that can serve as many as 19 machines and equipment. Among the machines and equipment that function is generally not meet the standards of processing to produce good product quality and capacity is very small, while for their operation need large energy so inefficiently. Other factors that cause machinery and equipment cocoa processing were not operated are the quality of raw materials was low, the quality of the powder and cocoa butter are produced not get the quality standard products as per SNI or health, production management is not running, there is no involvement of skilled personnel and experts in the industry and marketing, product and product quality is still not market-oriented and there is no involvement of capital providers